Global vegetation patterns of the past 140, 000 years. (16th July 2020) - Allen, Judy R. M.; Forrest, Matthew; Hickler, Thomas; Singarayer, Joy S.; Valdes, Paul J.; Huntley, Brian
Abstract: Aim: Insight into global biome responses to climatic and other environmental changes is essential to address key questions about past and future impacts of such changes. By simulating global biome patterns 140 ka to present, we aimed to address important questions about biome changes during this interval. Location: Global. Taxon: Spermatophyta. Methods: Using the LPJ‐GUESS dynamic global vegetation model, we made 89 simulations driven using ice‐core atmospheric CO2 concentrations, Earth's obliquity, and outputs from a pre‐industrial and 88 palaeoclimate experiments run using HadCM3. Experiments were run for 81 time slices between 1 and 140 ka, seven 'hosing' experiments also being run, using a 1‐Sv freshwater flux to the North Atlantic, for time slices corresponding to Heinrich Events H0–H6. Using a rule‐based approach, based on carbon mass and leaf area index of the LPJ‐GUESS plant functional types, the biome was inferred for each grid cell. Biomes were mapped, and the extent and total vegetation biomass of each biome, and total global vegetation biomass, estimated. Results: Substantial changes in biome extents and locations were found on all vegetated continents. Although the largest magnitude changes were in Eurasia, important changes were seen in tropical latitudes and the Southern Hemisphere. Total global extent of most biomes varied on multi‐millennial (orbital) time scales, although some (e.g. Tropical Raingreen Forest) responded principally to the c. 100‐kyr glacial–interglacial cycle and others (e.g. Temperate Broad‐leaved Evergreen Forest) mainly to the c. 20‐kyr precession cycle. Many also responded to millennial contrasts between stadial ('hosing') and interstadial climates, with some (e.g. Tropical Evergreen Forest) showing stronger responses than to the multi‐millennial changes. Main conclusions: No two time slices had identical biome patterns. Even equivalent Holocene and last interglacial time slices, and the last and penultimate glacial maxima, showed important differences. Only a small proportion of global land area experienced no biome change since 140 ka; many places experienced multiple biome changes. These modelling experiments provided little evidence for long‐term biome stability.